Accounting Study Program Student Readiness in Facing The World Of Work in The Society 5.0 Era - Risa Septiani; Nida Nusaibatul Adawiyah; Mufid Suryani; Cicilia Erly Istia (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The era of society 5.0 is the concept of technological development that increases automation and digitalization in the industrial and production sectors. The concept of society 5.0 states that technology will coexist with humans to improve the quality of life in a sustainable manner, including in the world of education. The aim of this research is to determine the readiness of Gunadarma University accounting study program students in facing the world of work in the era of society 5.0. This research uses a combined approach between qualitative and quantitative methods. The data used in this research is primary data. The variable used in this research is work readiness which focuses on the professional skills of an accountant. The indicators used are an adoption of IES 3 and the dimensions measured according to IAESB 2019 are intellectual, interpersonal and communication, personal and organizational. The results of the research show that the readiness of Gunadarma University accounting study program students to face the world of work in the era of society 5.0 obtained the highest results in the dimensions of interpersonal and communication skills, the second rank was personal skills, the third rank was the dimension of organizational skills and the fourth rank was the dimension of intellectual skills.